Gênero e educação a formação educacional para a igualdade de Gênero no Movimento dos Trabalhadores Rurais sem Terra - Pessôa, Jeniffer Ribeiro (Editora Oficina Universitária, 2022)
In addition to occupying, resisting and producing, MST women have been waging a tough "fight within the fight" to overcome sexism and promote gender equality. Gender education in the movement's schools, combined with struggles fought especially by women in assemblies, cooperatives and associations, in settlements, in addition to equal participation in the movement's strategic decisions have contributed to the construction of new social and gender relations. Patriarchy predates the capitalist mode of production, but capitalism has certainly deepened the differences between men and women, between peoples and ethnicities, and it has already been scientifically proven that it is impossible to achieve substantive equality between human beings within the framework of this barbaric mode of production. and petty. Women from all parts of Latin America are waging a fierce struggle against all forms of oppression that - who knows - could lead to a society beyond capital. Jeniffer Pessôa - in this careful research - makes a fundamental contribution to this debate by addressing the issues of gender, machismo and education in the MST. HENRIQUE TAHAN NOVAES | UNESP Marília